Perencanaan Lanskap Ekowisata Hutan Mangrove Di Pantai Sari Ringgung Desa Sidodadi Kecamatan Padang Cermin Kabupaten Pesawaran - Bagus Nugraha; Irwan Sukri Banuwa; Setyo Widagdo (Jurnal Sylva Lestari, 2015)
Ecotourism is a utilization of mangrove forest ecosystems in a sustainable manner through tourism activities that are responsible to environment. The application of the ecotourism concept in the mangrove forest area in Sari Ringgung Beach Sidodadi Village of Padang Cermin Pesawaran is expected to reduce the damage to mangrove ecosystems by increasing public awareness of the mangroves existence. This research objectives are to develop a plan of mangrove forest ecotourism through the exploration landscape potential in the form of biophysical elements and social community. Ecotourism planning activities consist of an potential inventory, analysis, synthesis, scheming concepts, and tread design. Inventory data results are categorized into the potential and constraints are analyzed logically to obtain the synthesis results. Space zoning development plan was produced at the planning stage as the basic design of the space concept, circulation paths, and green governance. Mangrove forest in Sari Ringgung Beach has ecotourism potential including physical and visual condition, plants diversity and mangrove wildlife animals, visitors crowd, and good community support. Ecotourism plan is designed by the spatial distribution of ecotourism into 15 ha as reception area, 2 ha as service area, 68 ha as buffer area, and 12 ha as ecotourism area. Ecotourism access is developed in three path circulation are: paving block path in the dry land route, boardwalk path to cross the wetlands, and ships route to cross the open beach. Coconut and Pine selected as a space filler plants and various types of mangrove as wetlands rehabilitation plants. Keywords: ecotourism, mangrove, landscape planning